Burial customs and religious concepts of the Early Iron Age in Northern Croatia - Potrebica, Hrvoje (Array, 2000)
The paper presents some characteristic religious and cult features of Hallstatt culture in northern Croatia. They can be seen on diverse parts of archaeological record, from ornaments on pottery to burial ritual and grave inventories. Some of those features belong to the classic elements of Hallstatt cult (water birds and bovids), but other elements show clear influences of other cultures, especially Greek and Etruscan (tripods and other pottery imitations of bronze vessels). Incineration and burial under tumuli are characteristic burial custom of Hallstatt in that area, but there are some special features concerning burial ritual as well as grave construction and inventory in some other neighbouring cultural groups. The most of the Hallstatt tumuli contain multiple graves, but most of the units (tumuli) are clearly dominated by one grave. The attribution of other graves within certain unit is connected to one of the most intriguing problems that will be discussed on conceptual level - human sacrifice. Some of the richest graves have distinctive warrior character. Warriors did not just dominate the social structure of the Hallstatt cultural groups; they were also present in their religious world. From their own concepts, under the influence of Greece, they formed some sort of cult of heroes reflected in special type and distribution of grave inventory. Special attention will also be given to other gender issues concerning cult. According to grave inventories, each unit (tumulus) can be attributed to one or the other gender. Especially interesting are those that have female characteristics. The inventory of these units suggests strong religious character, rather than high social value. That rises the interesting question of the role of women within the framework of Hallstatt religious concept.